Effects of ameliorant and fertilizer on the growth and yield of maize grown in peatlands soil of West Kalimantan Indonesia - Yance Waramui; Titiek Islami; S Sudiarso (Journal of Degraded and Mining Lands Management, 2019)
The use of agricultural lime ameliorant or rice husk charcoal combined with inorganic fertilizers is one of the agricultural intensification efforts in peatlands. This study aimed to find out the influence of various ameliorant types and nitrogen, phosphorus, and potassium inorganic fertilizer doses application on growth and yield of maize in peatlands soil was conducted in Siantan Hulu Village, Pontianak City, West Kalimantan used. This study used a split-plot design with the main plot of ameliorant types (A) consisting of three treatments i.e. without ameliorant (A0), agricultural lime of 3 t/ha (A1) and rice husk charcoal of 3 t/ha (A2). The subplot was inorganic fertilizer doses (B) consisting of three treatments i.e. B1 = 50% of N, P, and K inorganic fertilizers, B2 = 75% of N, P, and K inorganic fertilizer, and B3 = 100% of N, P, and K inorganic fertilizers. Observation on crop growth consisted of crop height, number of leaves, leaf area, crop total fresh weight, crop total dry weight, and crop growth rate. Yield observation consisted of ear length, ear diameter, 100-dry seed weight, seed yield weight per hectare, and harvest index (IP). The results of the study indicated that rice husk charcoal application of 3 t/ha gave seed yield weight of 7.25 t/ha that was higher than that of agricultural lime that produced 6.34 t/ha seed yield and without ameliorant that produced the lowest seed yield of 4.18 t/ha. Application of N, P, and K inorganic fertilizer dose of 75% produced an insignificant difference seed yield compared to the dose of 100%, which were 6.32 t/ha and 6.69 t/ha, respectively. Therefore, the application of N, P, and K inorganic fertilizer dose of 75% is recommended as a basic of maize fertilization.